Reversed iconoclasm: Tadeusz Różewicz seeks forms of an “inner image” - Agata Stankowska (Przestrzenie Teorii, 2014)
Tadeusz Różewicz often noted down phrases which could be interpreted as iconoclastic in his poems and poetry-related sketches. This article presents the reasons for the poet’s dislike of an image that is identified with a metaphor, which he expressed particularly strongly immediately after the war. It also describes the continuation of historical iconoclasm which was characteristic of the twentieth century, and on the level of which the notion of God’s “unrepresentability” was replaced by the issue of the unspeakableness and inconceivability of trauma. The efforts that Różewicz made to rethink the status of an image are presented against such a background. According to the poet, an image should satisfy the primeval desire for presence, which was ascribed to it once again after the Holocaust, like a painting from before the era of art. Therefore, Różewicz develops the theory of an “inner image” which one should pursue rather than create. An “inner image” is not a “fanfare played to celebrate life”, which inspires awe and can only be described in terms of aesthetic conventions, but a kind of manifestation of the hidden, wounded lyrical “I” and, most importantly, of its authentic experience. The “truth” of the image and metaphor that are “possible after Auschwitz” became bound up with what is somatic, and not conceptual, with what is tangible, and not imaginable, and with what is metonymic, not metaphorical. This truth is also largely (but not necessarily solely) connected with the human condition and existence rather than with God’s fullness.